Development and validation of a contextualized phubbing scale for Indonesian university students: A design-based research approach - Rizka Febrianti; Imalatul Khairat; Nina Fitriyani (ENLIGHTEN (Jurnal Bimbingan dan Konseling Islam), 2025)
Phubbing has become an increasingly widespread phenomenon among university students, driven by growing smartphone dependence in daily academic and social activities. Defined as the act of prioritizing smartphone use over face-to-face interaction, phubbing is associated with adverse outcomes, including impaired concentration, weakened social bonds, and diminished academic performance. However, existing instruments such as the Chotpitayasunondh & Douglas scale show limitations in item validity specifically items 5, 7, and 14 and lack contextual relevance for the Indonesian higher education population. Addressing this gap, the present study aimed to develop and validate a culturally contextualized phubbing scale tailored to Indonesian university students. Employing a Design-Based Research (DBR) methodology based on Reeves’ generic model, the study progressed through three iterative phases: analysis and exploration, design and construction, and evaluation and reflection. A total of 384 students from diverse Indonesian universities participated, selected via convenience sampling. The resulting instrument comprises 40 items spanning four core dimensions nomophobia, interpersonal conflict, self-isolation, and problem acknowledgment. All items demonstrated acceptable item-total correlations (>0.30), and the scale achieved high internal consistency (Cronbach’s α = 0.863). The validated scale offers a robust, context-sensitive tool for assessing phubbing behavior in Indonesian university settings and provides practical utility for educational counselors in designing targeted interventions to mitigate the psychological and academic risks associated with excessive smartphone use.